Measurement of Uranium Concentration in Some Soil Samples in Jalawla'a City Using CR-39 Detector - Mohammad, Ali M; Ahmed, Israa k; Ahmed, Yasir S (Al-Nahrain Journal of Science, 2013)
Abstract:In this study, the fission track registration technique with the CR-39 detector are using to determination the uranium concentrations for twenty-eight samples of soil distributed in seven districts in Jalawla'a City in Iraq by depth in 5cm. The uranium concentrations in soil samples measured by using fission tracks registration in (CR-39) track detector that caused by the bombardment of (U) with thermal neutrons from (241 Am-Be) neutron source that has flux of (5 ×103 n cm-2 s-1).The concentrations values were calculated by a comparison with standard samples. The results showed that the maximum value of uranium is (1.280 ppm) in Al-Talea district and the minimum is (0.719 ppm) in Al-Uruba district